Cervical cancer incidence, mortality, and burden in China: a time-trend analysis and comparison with England and India based on the global burden of disease study 2019 - Wu, Siyu; Jiao, Jun; Yue, Xiaoyu; Wang, Yaping (Frontiers in Public Health, 2024)
Background Cervical cancer is the fourth highest incidence of malignancy in the world and a common cause of cancer death in women. We assessed the trends of incidence and mortality and disability-adjusted life year (DALY) in China, England and India from 1990 to 2030. Method Data were obtained from the Global Burden of Disease (GBD) database. We collected the number and rate of incidence, death and DALY from 1990 to 2019 and calculated the estimated annual percentage change (EAPC). Further analysis was carried out by ages and years. We also collected attributable risk factors to cervical cancer. Finally, we utilized the Bayesian Age-Period-Cohort (BAPC) model to forecast trends in the rate of age-standardized incidence (ASIR) and age-standardized death (ASDR) the for the next decade. Result Globally, the incidence of cervical cancer cases increased from 335,641.56 in 1990 to 565,540.89 in 2019. In 2019, the ASIR and ASDR of cervical cancer were higher than those of India but lower than those of England. Furthermore, unsafe sex and smoking emerge as prominent risk factors for cervical cancer. Over the next decade, ASIR and ASDR are expected to decline in China and England, while India’s ASIR is still on an upward trend and ASDR is on a downward trend. Conclusion The epidemiological data of cervical cancer in these three countries reflects the influence of different stages of development and healthcare systems. Trends over the next decade suggest that China and India still face a huge burden of cervical cancer. When England has made significant progress, China and India need to take more measures to improve the prevention and control of cervical cancer.